Green Environmental Management Practices in Schools in The Implementation of the Deming Cycle: A Narrative Inquiry Approach - Ambar Sri Lestari; Imelda Wahyuni; Jumardin La Fua (School of Postgraduate Studies, Diponegoro Univer, 2024)
The aim of this research is to apply the Deming cycle to green environmental management to improve sustainable practices in schools. Using an inquiry-narrative approach by collecting data through semi-structured interviews with school principals, teachers, and students to explore green environmental management practices at Adiwiyata schools Analysis is carried out interpretatively by expanding, exploring, retelling, and fictionalising the data. The findings presented in green environmental management practices show four main themes in translating strategies into operational practices, including planning, implementation, learning, and action, to assist in identifying and analysing environmental practices reflectively. This research has implications for pro-environmental behaviour through a scientific approach to environmental management in schools.